Postnuptial Agreement Versus Kepentingan Kreditur - Elvina Elvina; Ari Wahyudi Hertanto (UNES Law Review, 2023)
Constitutional Court Decision Number 69/PUU-XIII/2015 allows married couples who are already married to enter into nuptial agreement. Previously such can only be carried upon before the marriage occurred. Thus, due to the enactment of this decision, legal problems arise as an impact upon how to provide legal protection for any third parties affected by implementation of court decision regarding the nuptial agreement. Problematical issues emerge against any third parties who hold security(ies), especially creditors as holders of mortgage, are vulnerable to losses possibility should the debtor defaults due to the unclear status of assets, which were previously included as joint assets and afterwards being dispatched after a nuptial agreement was made. This research was conducted in terms of normative juridical manner using a legal theory concept approach. The outcome of this research is to provide clarity on providing legal protection for creditors, as for creditors also need to be ensured that the publicity principle of the nuptial agreement is fulfilled. Notaries as officials who make and ratify nuptial agreements also need to apply the principle of prudence in carrying out their professional duties.